Electronic Strategic Intervention Material (e-SIM) in Grade 7 (Biology): Effects on Students’ Performance - Buitre, Shirlyn Lorenzana (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
As everyone is conforming to living with the pandemic, all offers and possible means in the education sector must be applied to help every learner manage their assignments. To help educators in assisting learners in doing their home works, DepEd Memo No. 177 s. 2005 -Training Workshop on Strategic Interventions for successful learning was created. This intervention aimed to enhance teachers’ skills in test analysis and interpretation and capacitate them in developing varied intervention materials for remediation and enrichment of knowledge. This training prompted the teachers to develop and use Strategic Intervention Material in teaching their subject areas. This study attempted to determine the effectiveness of electronic strategic intervention material in conducting remedial lessons in Grade 7 Biology in a public national high school, Division of Antipolo City for the school year 2022-2023. This study utilized Quasi-experimental research with Non-print Rating Sheets and pretest and posttest as data gathering instruments. Pretest and posttest were administered to thirty-five (35) Grade 7 students to measure their academic performance before and after the use of the Electronic Strategic Intervention Material. The findings showed that Science experts and teachers evaluated the e-SIM with grand mean ratings of 3.88 and 3.87, respectively, verbally interpreted as Very Satisfactory in terms of content quality, instructional quality, technical quality, and accuracy and up-to-datedness. Results also showed that there is a significant difference between the academic performance of the student respondents on the pretest and posttest after the utilization of e-SIM as revealed by the computed mean scores of 13.37 for the pretest and 34.77 for the posttest.